Morfologia facial e a apneia obstrutiva do sono - Santos, Anderson Capistrano Campos dos (2015)
The aim of this study was to evaluate the possible association between Facial Morphologic Patterns and Facial Types (Brachyfacial, Mesofacial and Dolichofacial) and Obstructive Sleep Apnea (OSA) patients of a sleep disorder center. For that, were used facial photographs of front, profile and smile of 260 individuals randomly selected among pacients attending a clinic specialized in polysomnography. For the establishment of the Facial Morphologic Diagnosis, the sample was sent to three experienced teachers of Orthodontics trained in the classification of Facial Pattern and each was instructed to rate the Facial Pattern using the following code: 1- Pattern I, 2 Pattern II, 3 Pattern III, 4- Long Face Pattern and 5- Short Face Pattern. The inter-rater reliability was assessed using the Kappa Index. The diagnosis of Facial Pattern was established through facial index (n-gn / zy-zy) which takes into account the ratio between the width and height of the face. The results showed that in the multiple linear regression model the Pattern II had the ability to worsen the apnea-hypopnea index (AHI) in 6.98 while Pattern III patients had this index attenuated in 11.45. Concerning the Facial Type, the Brachyfacial Type patients had an average AHI of 22.34 while the group classified as Dolichofacial Type showed a lower index of 10.52, with statistical significance. The morphological facial design was shown as a significant factor in aggravation or protection of OSA, as Brachyfacial Type and Pattern II individuals had higher AHI, while in Pattern III patients this index was reduced